The Application of Numbered Head Together to Strengthen the Students Character Building in Dempet - Nurul Chikmah; Murtono Murtono; Su’ad Su’ad (Jurnal Ilmiah Wahana Pendidikan, 2022)
The study aimed to explain how much influence the application of the Numbered Head Together learning model for strengthening the elementary school student character building in Dempet subdistrict. The research design used an experimental research. The study population was all of students in the fourth grade of elementary school. The sampling technique usesd purposive sampling. The research instrument used a questionaire. The collected data was tested with data description, normality test and homogeneity test, hypothesis test. The results obtained Sig. (2-tailed) of 00 <0.05 and the t-count of t (19.422) The value of t table with df = 91 of 1.9864, so that the t-count > t table (19.422> 1.9864). Sig. (2-tailed) <0.05. and the t-count > t table. It could be seen that there was significant influence on the Numbered Head Together method to strengthen the character building of the elementary school students